Growth Illusion in The Indonesia Stock Exchange: Relationship Between Earnings Management and Firm Value - Agus Satrya Wibowo; Fuad Fuad (The Indonesian Journal of Accounting Research, 2018)
Abstract: This research aimed to examine whether earnings management (EM) proxied with the practice of accrual management (AM) and real activity manipulations (RM) is related to the increase of firm value (FV) in the manufacturing industry in the IDX in the period 2010–2014. Subsequently, based on the normative and formal testing, the fixed effect model was selected as the appropriate model. The results of this empirical investigation indicate that an abnormal production cost (RMP) based RM practice tends to increase FV. Nevertheless, AM and abnormal discretionary expenses (RMD) based RM do not exhibit the same evidence. The results of the additional testing showed that the relationship between EM and FV differed when the firm was audited by an auditor affiliated with the big 4 auditors, when there was an institutional investor in the firm ownership and when IFRS was adopted. This research contributes to the literature on earnings management by suggesting that value creation drives the increase of FV by managers through the practices of RMP-based earnings management. The results indicate misinformation between the managers and the market, which makes FV growth become a mere illusion. Furthermore, the proposed model is expected contribute to researchers, regulators, investors, and analysts in evaluating the quality of accounting numbers and predicting the value relevance of earnings.Abstrak: Penelitian ini bertujuan untuk menguji apakah manajemen laba (EM) yang diproksikan dengan praktik manajemen akrual (AM) dan manipulasi aktivitas riil (RM) terkait dengan peningkatan nilai perusahaan (FV) dalam industri manufaktur di BEI di periode 2010–2014. Selanjutnya, berdasarkan pengujian normatif dan formal, fixed effect model dipilih sebagai model yang paling sesuai. Hasil dari investigasi empiris menunjukkan bahwa praktik RM berbasis abnormal production cost (RMP) cenderung meningkatkan FV. Namun demikian, AM dan RM berbasis abnormal discretionary expenses (RMD) tidak menunjukkan bukti yang sama. Hasil dari pengujian tambahan menunjukkan bahwa hubungan antara EM dan FV berbeda ketika perusahaan diaudit oleh auditor yang berafiliasi dengan auditor big 4, ketika adanya investor institusional di dalam kepemilikan perusahaan, dan ketika IFRS telah diadopsi. Penelitian ini berkontribusi pada literatur tentang manajemen laba dengan menunjukkan bahwa peningkatan FV didorong oleh penciptaan nilai melalui praktik manajemen laba berbasis RMP. Hasilnya menunjukkan mis-informasi antara manajer dan pasar menciptakan pertumbuhan FV hanya ilusi belaka. Selanjutnya, model yang diusulkan diharapkan dapat membantu peneliti, regulator, investor dan analis dalam mengevaluasi kualitas angka akuntansi dan memprediksi relevansi nilai atas laba perusahaan.